DIFFERENCES IN THE PROPERTIES AND DISTRIBUTION OF STRESS PRODUCED BY SEVERAL TYPES OF JOINTS IN STEEL CONSTRUCTION USING THE FINITE ELEMENT METHOD - Kritananda Tantra Halim; Edison Hatoguan Manurung (Journal of Moeslim Research Technik, 2025)
This study investigates the differences in mechanical behavior and stress distribution between two types of bolted steel connections—splice and endplate joints—using the Finite Element Method (FEM). Numerical simulations were conducted with MIDAS FEA NX, employing SS400 structural steel and A325 high-strength bolts to model beam connections subjected to bending loads. The analysis focused on evaluating von Mises stress distribution, deformation behavior, and load transfer mechanisms. Results showed that the endplate connection exhibited higher stiffness —approximately 5% less deflection than the splice connection —but also experienced 9.6% higher local stresses concentrated near the weld and in the outer bolt regions. Conversely, the splice connection exhibited a more uniform stress distribution and greater ductility, enabling controlled local yielding and improved energy dissipation. FEM predictions closely matched analytical beam theory with less than 5% deviation, confirming the accuracy of the numerical model. The findings suggest that endplate joints are suitable for rigid moment-resisting frames, while splice connections are preferable for applications requiring flexibility, fatigue resistance, and ease of assembly.